Pengaruh Market Requirement Dan Organizational Knowledge Terhadap Business Performance Bank (Unit Usaha Syariah) - Muhammad Amin (Eqien - Jurnal Ekonomi dan Bisnis, 2023)
ABSTRACK The research was conducted to determine the effect of market requirements and organizational knowledge on business performance of sharia business units owned by conventional banks in Indonesia. The research method used was a census of all conventional banks that have sharia business units in Indonesia, totaling 20 in the 2020 period. The data collected was analyzed using Smart Partial Least Square version 3.0. The result of the research is that there is a significant effect of market requirement and organizational knowledge variables on the business performance of sharia business units.